2017
DOI: 10.1590/s1678-9946201759079
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Leptospira isolates from humans and the environment in Uruguay

Abstract: Laboratory diagnosis of human leptospirosis usually relies on indirect methods exploring specific immune response. Isolation and identification of the involved strains are cumbersome, but can provide biological resources for pathogenic studies and relevant information for guiding prevention and control measures. The aim of the research we are hereby reporting was the characterization of Leptospira isolates obtained from humans and the environment in Uruguay. Blood cultures were performed from early samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…From the 12 lipL32 ‐positive samples, amplicons of rrs from urine (three samples from Farm I and four from Farm II) and one from kidney of one deceased lamb (Farm I), yielded sequences with 100% of identity to Leptospira interrogans . Phylogeny based on secY gene sequence analysis revealed that all eight sequences obtained directly from clinical samples and the sequences obtained from L. interrogans serovar Kennewicki isolates IP1712053 and IP1712058 cluster in one group, together with L. interrogans serovar Kennewicki previously isolated from cattle (Zarantonelli et al., ) and from a rural worker (Meny et al., ) in Uruguay, as well as with a reference strain L. interrogans serovar Pomona (Figure ).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…From the 12 lipL32 ‐positive samples, amplicons of rrs from urine (three samples from Farm I and four from Farm II) and one from kidney of one deceased lamb (Farm I), yielded sequences with 100% of identity to Leptospira interrogans . Phylogeny based on secY gene sequence analysis revealed that all eight sequences obtained directly from clinical samples and the sequences obtained from L. interrogans serovar Kennewicki isolates IP1712053 and IP1712058 cluster in one group, together with L. interrogans serovar Kennewicki previously isolated from cattle (Zarantonelli et al., ) and from a rural worker (Meny et al., ) in Uruguay, as well as with a reference strain L. interrogans serovar Pomona (Figure ).…”
Section: Resultsmentioning
confidence: 92%
“…Three of the 10 sera tested on Farm II were positive against serogroup Pomona, with titres ranging from 50 to 3,200 (Table 1). interrogans serovar Kennewicki isolates IP1712053 and IP1712058 cluster in one group, together with L. interrogans serovar Kennewicki previously isolated from cattle (Zarantonelli et al, 2018) and from a rural worker (Meny et al, 2017) in Uruguay, as well as with a reference strain L. interrogans serovar Pomona (Figure 2).…”
Section: Serologymentioning
confidence: 78%
See 2 more Smart Citations
“…All three species have been previously isolated and identified from humans, animals or the environment in Malaysia. L. kirschneri and L. interrogans, the most common and widely distributed Leptospira species from rodents and small mammals [13,30,[47][48][49][50][51] were identified as the main human-infecting Leptospira species in Malaysia based on our study. L. wolffii, an intermediate species was detected in the blood of two patients.…”
Section: Discussionmentioning
confidence: 97%